Cerebellar contributions to cognition in corticobasal syndrome and progressive supranuclear palsy. Issue 2 (16th November 2020) - Tse, Nga Yan; Chen, Yu; Irish, Muireann; Cordato, Nicholas J; Landin-Romero, Ramon; Hodges, John R; Piguet, Olivier; Ahmed, Rebekah M
Abstract: Mounting evidence suggests an association between cerebellar atrophy and cognitive impairment in the main frontotemporal dementia syndromes. In contrast, whether cerebellar atrophy is present in the motor syndromes associated with frontotemporal lobar degeneration (corticobasal syndrome and progressive supranuclear palsy) and the extent of its contribution to their cognitive profile remain poorly understood. The current study aimed to comprehensively chart profiles of cognitive impairment in relation to cerebellar atrophy in 49 dementia patients (corticobasal syndrome = 33; progressive supranuclear palsy = 16) compared to 33 age-, sex- and education-matched healthy controls. Relative to controls, corticobasal syndrome and progressive supranuclear palsy patients demonstrated characteristic cognitive impairment, spanning the majority of cognitive domains including attention and processing speed, language, working memory, and executive function with relative preservation of verbal and nonverbal memory. Voxel-based morphometry analysis revealed largely overlapping patterns of cerebellar atrophy in corticobasal syndrome and progressive supranuclear palsy relative to controls, primarily involving bilateral Crus II extending into adjacent lobules VIIb and VIIIa. After controlling for overall cerebral atrophy and disease duration, exploratory voxel-wise general linear model analysis revealed distinct cerebellar subregions differentially implicated across cognitive domains in each patient group. In corticobasal syndrome, reduction in grey matter intensity in the left Crus I was significantly correlated with executive dysfunction. In progressive supranuclear palsy, integrity of the vermis and adjacent right lobules I–IV was significantly associated with language performance. These results are consistent with the well-established role of Crus I in executive functions and provide further supporting evidence for vermal involvement in cognitive processing. The current study presents the first detailed exploration of the role of cerebellar atrophy in cognitive deficits in corticobasal syndrome and progressive supranuclear palsy, offering insights into the cerebellum's contribution to cognitive processing even in neurodegenerative syndromes characterized by motor impairment. Abstract : Voxel-based morphometry analysis revealed that cerebellar atrophy in the left Crus I was correlated with executive dysfunction in corticobasal syndrome, whereas the vermis and adjacent right lobules I–IV were associated with language performance in progressive supranuclear palsy, demonstrating cerebellar contributions to cognition even in neurodegenerative syndromes characterized by motor impairment. Graphical Abstract: